Can Entrepreneurship Training Improve Work Opportunities for College Graduates? - World Bank (Washington, DC, 2014)
Improving educational achievement for youth doesn't always result in better employment opportunities, and this can be especially acute in developing countries. As the World Bank's 2013 world development report highlights, the mismatch between the skills and aspirations of college graduates and the realities of labor markets not only limits a country's economic development, but also affects social cohesion. Joblessness and underemployment are viewed as some of the triggers of the Arab Spring, which started with Tunisia's jasmine revolution in early 2011. In Tunisia, the World Bank worked with the government to evaluate a program designed to give university students entrepreneurship training and assistance developing a business plan. The evaluation found that the program increased self-employment and helped students develop some skills associated with successful entrepreneurship. The lessons learned from the evaluation will help policymakers and development experts hone programs that deliver an impact.